Extraction of phenolic compounds from Chlorella sp. microalgae using pressurized hot water: kinetics study - Zakaria, Siti Maisurah; Mustapa Kamal, Siti Mazlina; Harun, Mohd Razif; Omar, Rozita; Siajam, Shamsul Izhar (Springer, 2022)
Chlorella sp. are among the highest cultivated species of microalgae. They are considered as an important functional food due to their abundance and valuable health benefits. It would be useful to develop an effective method for phenolic compound extraction from Chlorella sp. using safe technology and green solvents for the applications in food and pharmaceutical fields. Pressurized hot water extraction (PHWE) is an alternative for this purpose. PHWE was employed to extract phenolic compounds from Chlorella sp. microalgae at temperatures between 100 and 250 °C. The data collected is used to create the kinetics of the extraction process. The kinetics studies revealed that the extraction from Chlorella sp. microalgae using pressurized hot water treatment follows first-order kinetics and is strongly dependent on temperature. An increasing trend in the calculated values of mass transfer coefficient, k, was noticed, with increasing temperature. The activation energy, Ea, was calculated as 11.146 kJ/mol for the extraction treatment.